Change in Human Technology's Publisher: Continued focus on open access human–technology research - Tyrväinen, Pasi (Human Technology, 2016)
Beginning January 1, 2017, the role of publisher of the journal Human Technology will be moved from the Agora Center to the Open Science Center at the University of Jyvaskyla because of internal university restructuring. Day-to-day operations and ongoing open access will continue for Human Technology's without interruption.